Answer:
[tex]\huge\boxed{\bf\:x = 12, \:3}[/tex]
Step-by-step explanation:
[tex]x - 6 = \sqrt{3x}[/tex]
By squaring on both the sides,
[tex](x - 6)^{2} = (\sqrt{3x} )^{2}\\[/tex]
Now simplify it using the algebraic identity ⟶ (x - y)² = x² - 2xy + y². Also remember that when we square a square root the root in it will get removed.
[tex]x^{2} - (2*x *6) + 6^{2} = 3x\\x^{2} - 12x + 36 = 3x\\x^{2} + 36 = 3x + 12x\\x^{2} + 36 = 15x[/tex]
We can change the result into the following form [tex]\downarrow[/tex]
[tex]x^{2} + 36 - 15x = 0\\x^{2} - 15x + 36 = 0[/tex]
Now, this is in the standard form of a quadratic equation. Let's solve this further by using the splitting-the-middle-term method.
[tex]x ^ { 2 } -15x+36=0\\x^{2} - 12x - 3x + 36 = 0\\x(x - 12) - 3 (x - 12) = 0\\(x - 12)(x - 3) = 0[/tex]
Then, the values of x are:
[tex](x - 12) = 0\\\boxed{x = 12}\\\\\\(x - 3) = 0\\\boxed{x = 3}[/tex]
[tex]\rule{150}{2}[/tex]
Standard Form of a Quadratic Equation:
Splitting-the-middle-term Method:
[tex]\rule{150}{2}[/tex]